Facile Conjugated‐Polymer‐Based Flexible Lighting Fabrication and Microdeformation Monitoring. Issue 10 (28th June 2022) - Gao, Yifan; Wang, Min; Zhang, Zhen; Liu, Yaming; Hu, Shaowei; Liu, Gaixia; Ji, Hongjun; Zhao, Weiwei; Ma, Xing; Zhang, Jiaheng; Li, Mingyu; Wei, Jun; et al.
Abstract : Conjugated polymers (CPs) are an active research area and have been commonly used in optoelectronic devices, anticounterfeiting, bioimaging, and drug delivery due to their outstanding properties, such as a high quantum yield, photothermal stability, tunable spectra, and good biocompatibility. However, there have only been a few reports regarding flexible lighting due to the insoluble conjugated structure of CPs. Herein, a facile microemulsion method is used to solve the insolubility issue and fabricate CP nanoparticles for flexible lighting and microdeformation monitoring via high‐resolution inkjet printing. These CP nanoparticles are tuned to emit white light (color coordinates are (0.35, 0.35), and the correlated color temperature is 4810 K) by adjusting the CP ratios and polystyrene content. A CP‐based white light‐emitting diode (WLED) with a high color‐rendering index (up to 95) can be fabricated by coating these nanoparticles onto an ultraviolet light‐emitting diode (UVLED). At a driving current of 30 mA, the luminous efficacy of this WLED is 64 lm W −1 for at least 100 h. The resolution of the printing array is ≈40 μm (635 dots in −1 ), which can be used to detect 2 μm irreversible microdeformation. This approach may broaden the applications of CPs for flexible lighting and microdeformation monitoring. Abstract : Conjugated polymer nanoparticles are made through the microemulsion method. By using the cascaded fluorescence resonance energy transfer, these nanoparticles can emit white light, enabling a conjugated‐polymer‐based white light‐emitting diode with a high color‐rendering index, luminous efficacy, and excellent durability to be created. These nanoparticles can print high‐resolution arrays for flexible lighting and micro‐deformation monitoring.